Open government data publication and use in a developing country: a case of Ghana - Nuhu, Hubeidatu (Department of Information Systems, 2022)
Implementing Open Government Data (OGD) increases a government's ability to share data on its activities with citizens in machine-readable formats. OGD improves citizen participation, transparency, accountability and creates impact. By permitting more transparency, OGD helps citizens monitor government activities, which contributes to minimizing corruption. For example, while Also, OGD enables governments to track the impact of their actions; it gives citizens the ability to monitor government activities and critique where necessary. In addition, institutionalizing OGD by governments encourages economic growth and creates employment for citizens. The aim of this study is to examine OGD as a phenomenon in Ghana by focusing on how social factors either constrained or enabled the publication and use of OGD in Ghana. The investigation also examined how these social factors were created and sustained over time, influencing OGD institutionalization. The Structuration Theory was used as the primary theoretical lens to aid in understanding these social factors. In addition, the Structuration Theory was supplemented with concepts from Network Power, Ownership, and the Public Value Frameworks to provide additional theoretical categorization for the empirical findings. This study adopted a qualitative interpretive approach. Data sources for the research included semi-structured interviews, observations, and secondary data. The primary sources of data included Data Users, Data Publishers, Data “controllers,” and beneficiaries. The main findings from the study indicated that despite Ghana's long-standing democracy and being one of the early implementers of OGD, the phenomenon was yet to be institutionalized in the country. Data ownership, data quality, regulatory mandate, data sharing culture, control, and resources were the core social factors that influenced OGD publication. The meanings that actors ascribed to data ownership resulted in establishing and maintaining bureaucratic structures that allowed institutions and individuals to control available data. The actual use of OGD was influenced by social factors such as alliances/network creation, resources, power in networks, informal networks, and data quality assessment. Conversely, factors like alliances/network creation and technological resources acted as enablers that helped data users access the data. Data Users relied on technology and constantly drew upon their knowledge and understanding of technology and social connections to enable them to access and use data. They also relied on their ability to use technology to scrutinize data to ensure that it was of good quality and its use could create an impact or public value. Specific recommendations of this study include the need to use change management strategies targeted at all actors and institutions in the OGD ecosystem; educating and sensitizing actors on the relevance of making data technically available on a single approved web portal; and the creation of a context specific data quality indicators.